The Role of Law in Protecting Vulnerable Groups: A Study of Access to Justice for Marginalized Communities - Maaroef, Yusran; Balebu, Ester; Salintobe, Olivia (PT. Anagata Sembagi Education, 2025)
This article examines the role of law in protecting vulnerable groups in Indonesia and evaluates the structural, institutional, and cultural barriers that limit their access to justice. Using a normative juridical method, combined with constitutional analysis and vulnerability theory, the study demonstrates that while Indonesia’s Constitution and statutory frameworks provide robust guarantees of equality and human rights, vulnerable communities continue to experience procedural disadvantages, discrimination, and institutional exclusion. The findings show that barriers arise from financial constraints, geographic disparities, institutional bias, evidentiary burdens, corruption, and fragmented sectoral regulation. These structural obstacles prevent marginalized individuals from realizing substantive equality despite formal legal protections. The article argues that improving justice accessibility requires a combination of institutional reforms, including stronger legal aid implementation, inclusive policymaking, enhanced oversight mechanisms, digital justice innovations, and harmonized regulations aligned with international human rights standards. Ultimately, the law can only function as a protective instrument for vulnerable groups if constitutional commitments are matched by responsive institutions and culturally informed legal practices. Ensuring justice for marginalized communities therefore requires sustained reforms that integrate legal, institutional, and social strategies to achieve dignity, fairness, and equal treatment.